RCVS–TCH score can predict reversible cerebral vasoconstriction syndrome in patients with thunderclap headache - Soohyun Cho (Nature Portfolio, 2021)
Abstract Reversible cerebral vasoconstriction syndrome (RCVS) is one of the most important differential diagnosis in patients with thunderclap headache (TCH). We aimed to develop a new scoring system for RCVS in patients with TCH. We retrospectively analyzed 72 patients enrolled in the prospective study of TCH conducted in 2015–2016 (derivation set). We identified possible predictors for the diagnosis of RCVS and constructed a prediction model (RCVS–TCH score) using the multivariable logistic regression model. Diagnostic performance was validated to an independent validation set from our headache registry. The derivation set comprised 41 patients with RCVS and 31 with non-RCVS, and the validation set included 253 patients with TCH (165 with RCVS and 88 with non-RCVS). The RCVS–TCH score (range: 0–12) contained four predictors: recurrent TCHs, female sex, triggering factor for TCH (single or multi) and blood pressure surge. The C-index of RCVS–TCH score was 0.929 (95% CI = 0.874–0.984). The RCVS–TCH score ≥ 7 had a sensitivity of 80% and a specificity of 97% in discriminating RCVS from non-RCVS. In the validation set, RCVS–TCH score showed a C-index of 0.861 (95% CI = 0.815–0.908). In our study, the RCVS–TCH showed good performance, which may aid the diagnosis of RCVS among patients with TCH.